Public policy for family farming. Definition for better support - Sourisseau, Jean-Michel; Bélières, Jean-François; Bonnal, Philippe; Bosc, Pierre-Marie; Losch, Bruno; Marzin, Jacques (Perspective, 2014)
Version française de l'article Versión en español del artículo Versão portuguesa do artigo <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"The International Year of Family Farming has focused world attention on the economic and social role played by this type of agriculture, as well as on its potential for meeting global challenges. It has also identified weaknesses and the need for decisive, far-reaching public action to overcome these. However, policy making and implementation require a clear-cut statistical definition of family farming at the global level, as well as a detailed picture of the various forms this agriculture may take at the national level. Hence the proposal to characterise family farming by the conjunction between the domestic unit and the production unit, and to determine criteria for fine-tuning this definition in each country."}" data-sheets-userformat="{"2":577,"3":[null,0],"9":0,"12":0}">The International Year of Family Farming has focused world attention on the economic and social role played by this type of agriculture, as well as on its potential for meeting global challenges. It has also identified weaknesses and the need for decisive, far-reaching public action to overcome these. However, policy making and implementation require a clear-cut statistical definition of family farming at the global level, as well as a detailed picture of the various forms this agriculture may take at the national level. Hence the proposal to characterise family farming by the conjunction between the domestic unit and the production unit, and to determine criteria for fine-tuning this definition in each country.